Multiple failures of API 5L X42 natural gas pipe: Experimental and computational analysis - Mohsin R.; Majid Z.A.; Yusof M.Z. (2023)
Multiple failures of API 5L X42 (X42) coal-tar coated natural gas feeder line due to vertical jetting of high pressure erosive slurry was studied experimentally and computationally. Computational Fluid Dynamic (CFD) was used as the simulation tools to study the flow pattern, velocity distribution and strain rates on pipe surface. Experimental work was performed to determine the erosion pattern. Three different diameters of jetting sources produced three distinct impact patterns were clearly identified. These patterns were frequently referred in the experimental study. A CFD simulation result shows that the highest shear strain rate area coincides with the leakage point. These results thus support the hypothesis that it is very likely that the failure of the gas pipeline was caused by the high pressure water jet gusting from the failed welded joint of the water pipeline. 2013 Elsevier Ltd.